Quality vaccines for all people: Report on the 16th annual general meeting of the Developing Countries Vaccine Manufacturers' Network, 05–07th October 2015, Bangkok, Thailand. Issue 31 (30th June 2016) - ,; Homma, Akira; Meng, Li; Suhardono, Mahendra; Tippoo, Patrick; Jadhav, Suresh; Gao, Steven; Prasad, Ray; Suri, Rajinder K.; Thai, Pan Hong; Vonghangool, Vitoon; Pagliusi, Sonia; et al.
Abstract: The Developing Countries Vaccine Manufacturers Network (DCVMN) assembled high-profile leaders from global health organisations and vaccine manufactures for its 16th Annual General Meeting to work towards a common goal: providing quality vaccines for all people. Vaccines contribute to a healthy community and robust health system; the Ebola outbreak has raised awareness of the threat and damage one single infectious disease can make, and it is clear that the world was not prepared. However, more research to better understand emerging infectious agents might lead to suitable vaccines which help prevent future outbreaks. DCVMN members presented their progress in developing novel vaccines against Dengue, HPV, Chikungunya, Cholera, cell-based influenza and other vaccines, demonstrating the commitment towards eliminating and eradicating preventable diseases worldwide through global collaboration and technology transfer. The successful introduction of novel Sabin-IPV and Oral Cholera vaccine in China and Korea respectively in 2015 was highlighted. In order to achieve global immunisation, local authorities and community leaders play an important role in the decision-making in vaccine introduction and uptake, based on the ability of vaccines to protect vaccinated people and protect non-vaccinated in the community through herd immunity. Reducing the risk of vaccine shortages can also be achieved by increasing regulatory convergence at regional and international levels. Combatting preventable diseases remains challenging, and collective efforts for improving multi-centre clinical trials, creating regional vaccine security strategies, fostering developing vaccine markets and procurement, and building trust in vaccines were discussed.